Spatial and temporal dynamics of aufeis in the Tso Moriri basin, eastern Ladakh, India - Brombierstäudl, Dagmar; Schmidt, Susanne; Nüsser, Marcus (Permafrost and periglacial processes, 2023)
Aufeis is a common phenomenon in cold regions of the Northern Hemisphere that develops during winter by successive water overflow and freezing on ice-covered surfaces. Most studies on aufeis occurrence focus on regions in North America and Siberia, while research in High Mountain Asia (HMA) is still in an exploratory phase. This study investigates the extent and dynamics of icing processes and aufeis in the Tso Moriri basin, eastern Ladakh, India. Based on a combination of 235 Landsat 5 TM/8 OLI and Sentinel-2 imagery from 2008 to 2021 the occurrence of icing and aufeis was classified using a random forest classifier. A total of 27 frequently occurring aufeis fields with an average maximum extent of 9 km2 were identified, located at a mean elevation of 4,700 m a.s.l. Temporal patterns show a distinct accumulation phase (icing) between November and April, and a melting phase lasting from May until July. Icing is characterized by high seasonal and inter-annual variability. Successive water overflow mainly occurs between January and March and seems to be related to diurnal freeze-thaw-cycles, whereas higher daytime temperatures result in larger icing areas. Aufeis feeding sources are often located within or in close vicinity to wetland areas, while vegetation is largely absent on surfaces with frequent aufeis formation. These interactions require more attention in future research. In addition, this study shows the high potential of a machine learning approach to monitor icing processes and aufeis, which can be transferred to other regions.